Building Without Borders : Sustainable Construction for the Global Village. - Kennedy, Joe (Natural Building Series., 2009)
Building Without Borders describes pioneering efforts to create sustainable shelter for billions currently under-housed. It surveys projects around the world that are housing the homeless without destroying natural habitats to do so, by drawing upon local traditions such as bamboo, straw bale and earthen construction. Highly illustrated and popular in style, it includes case studies, technical information, and the latest thinking on truly sustainable construction, and advocates education and training as the means to empower local peoples to create houses for themselves. Joseph F. Kennedy cofoun.